2000
DOI: 10.2527/2000.7871852x
|View full text |Cite
|
Sign up to set email alerts
|

National Beef Tenderness Survey-1998.

Abstract: Fifty-six retail stores representing 15 retail chains and 14 foodservice facilities in eight U.S. cities were sampled to determine the tenderness of beef steaks at retail and foodservice levels based on Warner-Bratzler shear (WBS) values and consumer evaluation panels. Retail consumer panels were conducted at five universities. Each retail and foodservice steak was evaluated using 10-point scales. Steaks were divided into the following quality groups for statistical analysis: Prime, Top Choice, Choice, Select,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
91
3
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 0 publications
11
91
3
2
Order By: Relevance
“…Postfabrication aging times for foodservice subprimals (Table 2) showed that the mean aging time was 30.1 d. This is very similar to the times reported by Brooks et al (2000) with the mean aging time being 32 d. The shortest aging time, 7 d, was found for some ribeyes, whereas the longest aging time, 136 d, was observed for some strip loins. These data show a much wider range in aging time than did Brooks et al (2000).…”
Section: Postfabrication Aging Timessupporting
confidence: 80%
See 2 more Smart Citations
“…Postfabrication aging times for foodservice subprimals (Table 2) showed that the mean aging time was 30.1 d. This is very similar to the times reported by Brooks et al (2000) with the mean aging time being 32 d. The shortest aging time, 7 d, was found for some ribeyes, whereas the longest aging time, 136 d, was observed for some strip loins. These data show a much wider range in aging time than did Brooks et al (2000).…”
Section: Postfabrication Aging Timessupporting
confidence: 80%
“…Subprimal postfabrication times at the retail level aver aged 22.6 d (Table 1) and the range was 3-83 d. These data are similar to those found by Morgan et al (1991) with a range of 3-90 d and are greater than those reported by Brooks et al (2000) with the range of 2-61 d. Bone-in ribeyes possessed the lowest percentage of boxes aged under 14 d, whereas top rounds had the largest percentage. The mean percentage of subprimals aged under 14 d was 19.6, which was considerably lower than the 34.1% in the NBTS-1998 (Brooks et al, 2000).…”
Section: Postfabrication Aging Timessupporting
confidence: 77%
See 1 more Smart Citation
“…In Poland, the above-mentioned trend is associated with an increase in beef export and a rise in beef prices, which may have contributed to the price's greater role as a determinant of attitude (McCarthy et al 2003). Moreover, unpopular beef quality (Węglarz 2010) and lack of knowledge regarding the influence of the thermal treatment method on beef quality (Brooks et al 2000) may be factors inducing the low demand for beef in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…The National Beef Quality Audits (Lorenzen et al, 1993), 1995 (Boleman et al, 1998), and 2000(McKenna et al, 2002 and National Beef Tenderness Surveys conducted in 1991 (Morgan et al, 1991) and 1998 (Brooks et al, 2000) identified the lack of tenderness as a major concern for the beef industry. Currently, the USDA grading system does not include a direct measure of tenderness.…”
Section: Introductionmentioning
confidence: 99%